WOMEN WRITERS IN ENGLISH LITERATURE - Saparbayeva Muxlisa Umidbek qizi; Kobilova Nafisa Raimovna (Лучшие интеллектуальные исследования, 2024)
Annotation: This article examines the character of female writers in English prose. Each nation describes the image of a woman differently in its literature based on its national views. In English literature a woman considered as a business woman,an entrepreneur,a worker, a person with her own profession. The image of women in English literature has gradually changed over time. English writers tried to express the best features in female characters. English women writers have written some of the world’s greatest and best-selling books and they are very popular. We will get acquainted with some of them in this article.